The role of nest surface temperatures and the brain in influencing ant metabolic rates. (August 2016) - Andrew, Nigel R.; Ghaedi, Behnaz; Groenewald, Berlizé
Abstract: Thermal limits of insects can be influenced by recent thermal history: here we used thermolimit respirometry to determine metabolic rate responses and thermal limits of the dominant meat ant, Iridomyrmex purpureus. Firstly, we tested the hypothesis that nest surface temperatures have a pervasive influence on thermal limits. Metabolic rates and activity of freshly field collected individuals were measured continuously while ramping temperatures from 44 °C to 62 °C at 0.25 °C/minute. At all the stages of thermolimit respirometry, metabolic rates were independent of nest surface temperatures, and CTmax did not differ between ants collected from nest with different surface temperatures. Secondly, we tested the effect of brain control on upper thermal limits of meat ants via ant decapitation experiments ('headedness'). Decapitated ants exhibited similar upper critical temperature (CTmax ) results to living ants (Decapitated 50.3±1.2 °C: Living 50.1±1.8 °C). Throughout the temperature ramping process, 'headedness' had a significant effect on metabolic rate in total (Decapitated V̇ CO2 140±30 µl CO2 mg −1 min −1 : Living V̇ CO2 250±50 CO2 mg −1 min −1 ), as well as at temperatures below and above CTmax . At high temperatures (>44 °C) pre- CTmax the relationships between I. purpureus CTmax values and mass specific metabolic rates for living ants exhibited a negative slope whilst decapitated ants exhibited a positive slope. The decapitated ants also had a significantly higher Q10 :25–35 °C when compared to living ants (1.91±0.43 vs. 1.29±0.35). Our findings suggest that physiological responses of ants may be able to cope with increasing surface temperatures, as shown by metabolic rates across the thermolimit continuum, making them physiologically resilient to a rapidly changing climate. We also demonstrate that the brain plays a role in respiration, but critical thermal limits are independent of respiration levels. Graphical abstract: Highlights: We determine metabolic rate responses and thermal limits of Iridomyrmex purpureus. Metabolic rates were independent of nest surface temperatures. Decapitated ants exhibited similar upper critical temperature results to living ants. Critical thermal limits are independent of respiration levels. Negative effects of increasing temps could be reduced via metabolic efficiency.